Clinical stability, diagnosis and catchment area: the patients of a university-based psychiatric outpatient clinic - Iraneide Castro de Oliveira; Isabella Nascimento; Evandro Silva Freire Coutinho; Vanessa Andrade Martins Pinto; Andrea Vilanova; José Carlos Appolinario; Maria Tavares Cavalcanti (Jornal Brasileiro de Psiquiatria)
ABSTRACT Objective This study aimed to characterize the patients assisted at the general outpatient clinic of the Psychiatry Institute of Universidade Federal do Rio de Janeiro (IPUB-UFRJ) and to assess these patients’ clinical stability. Methods This cross-sectional study collected information using a structured questionnaire filled in by the patient’s physician. The questionnaire, specifically developed for this purpose, included sociodemographic data; the dwelling area; psychiatric diagnosis according to ICD-10; clinical stability assessment by means of five psychiatric instability criteria and the physician’s global clinical impression over the six previous months. Clinical stability was defined as a negative answer to all five pre-defined instability criteria. Results Overall, 1,447 questionnaires were filled in. The sample was composed of 824 (57%) women; with an average age of 49 years; 1,104 (76.3%) patients lived in the city of Rio de Janeiro and 343 (23.7%) lived outside the city; 983 (67.9%) patients had a severe mental disorder (SMD) diagnosis and 946 (65.3%) patients were considered stable. Statistically, the clinical stability by dwelling area did not differ. The most frequent clinical instability criterion was “exacerbation or emergence of acute manifestations of the disease”. Conclusion The major part of the patients displayed a SMD and was considered clinically stable.